2013
DOI: 10.3906/bot-1302-41
|View full text |Cite
|
Sign up to set email alerts
|

The revision of genus Seseli (Umbelliferae) in Turkey

Abstract: Seseli tortuosum was introduced as the lectotype of Seseli (Linnaeus, 1754). Several studies have been conducted on Turkish Seseli after the publication of the 11th volume of the Flora of Turkey. Pimenov and Leonov reported the total number of taxa attributed to Seseli (Pimenov and Leonov, 2004). In another study, Pimenov and Kljuykov transferred S. peucedanoides (M.Bieb.) Koso-Pol. and S. foliosum (Sommier & Levier) Manden to the genus Gasparrinia Bertol. Moreover, they placed S. campestre Besser in the synon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…In most cases, the researchers investigated species indigenous to a local area, region or country. For instance, Perveen and Qaiser (2006) studied species from Pakistan, Yousefzadi et al (2006) and Amjad and Akkafi (2012) species from Iran, Pehlivan et al (2009), Mungan et al (2011), Dogan Guner et al (2011 and Yilmas and Tekin (2013) those from Turkey and De Leonardis et al (2008Leonardis et al ( , 2009) species from Italy. However, only a few palynological studies concerning the genus Chaerophyllum, including the following 7 species have been carried out: C. astrantiae…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the researchers investigated species indigenous to a local area, region or country. For instance, Perveen and Qaiser (2006) studied species from Pakistan, Yousefzadi et al (2006) and Amjad and Akkafi (2012) species from Iran, Pehlivan et al (2009), Mungan et al (2011), Dogan Guner et al (2011 and Yilmas and Tekin (2013) those from Turkey and De Leonardis et al (2008Leonardis et al ( , 2009) species from Italy. However, only a few palynological studies concerning the genus Chaerophyllum, including the following 7 species have been carried out: C. astrantiae…”
Section: Introductionmentioning
confidence: 99%
“…Study of the descriptions in Hedge and Lamond (1972), Davis et al (1988), Duman (2000), Ball (1968), Rechinger (1987), Parolly and Nordt (2001), Shishkin (1950), Özhatay et al (2009), Doğan Güner and Duman (2013) as well as comparison with herbarium material in GAZI, HUB, KNYA and ANK revealed that the specimens indeed represented a new taxon. In particular, the new taxon was compared with the closely similar taxa Seseli gummiferum Pall.…”
Section: Methodsmentioning
confidence: 94%
“…After that Seseli ramosissimum replaced with Seseli hartvigiii by Parolly (Parolly and Nordt 2001). Latest revision of Seseli in Turkey was made by Doğan Güner and Duman (2013). So the total number of these taxa is 13 now.…”
Section: Introductionmentioning
confidence: 99%
“…SEM analysis of mericarp micromorphology was conducted with the same method. The terminology of the pollen and mericarp is based on Moore et al 1991, Punt et al (2007), and Doğan Güner et al (2011).…”
Section: Methodsmentioning
confidence: 99%